FACTORS RELATED TO MULTIDIMENSIONAL FRAGILITY IN ELDERLY PEOPLE. - da Conceição Alves Faria, Ana; Ferreira Pereira da Silva Martins, Maria Manuela; Laredo Aguilera, José Alberto; Pimenta Lopes Ribeiro, Olga Maria; Almeida Ventura da Silva, João Miguel; Faria Fonseca, Esmeralda; Moreira Ferreira, Luciano José (Revista Baiana de Enfermagem, 2022)
Objective: to analyze the sociodemographic and health factors related to multidimensional frailty in elderly people living at home. Method: descriptive, exploratory and cross-sectional study, which evaluated 300 elderly enrolled in a Health Unit in the Northern Region of Portugal. The sociodemographic and health conditions of the old people were analyzed, with application of the Tilburg Frailty Index, Falls Efficacy Scale International – 7 items, Barthel Index and Lawton and Brody Scale. Results: in the elderly in the study, with a mean age of 81.34±6.75 years, frailty was identified in 60.33%. The related factors were: gender, marital status, self-perceived health, pathological history, severe disease in the last year, polymedication, falls, fear of falling and higher level of dependence. Conclusion: multidimensional frailty of the elderly living at home is a prevalent condition. When predictor factors in primary health care are analyzed early, it is possible to intervene in order to delay this syndrome.